(untitled) (Sains Humanika, 2018)
The allocation of workers’ health expenditure is a major issue to employers in Malaysia, especially SOCSO, as it is closely related to the performance and welfare of workers. Work injury and occupational disease require employers to allocate substantial costs to compensate the disability benefits and benefits of dependents or pensions. This study aims to identify the level and trend of health expenditure for employees covered under Employment Injury Scheme (EIS) in the Malaysia Social Security Organisation (SOCSO) for years 2009-2013. Retrospective descriptive analysis is carried out on a 5-year data (2009-2013) which comprises all employees who contribute under the SBP. Based on the descriptive analysis, the number of active workers contributing to SOCSO and the amount of benefits paid by SOCSO are increasing every year. Based on the Temporary Disability (HUS) data, the number of working days lost due to accidents is different according to gender and age, with more male workers than female workers, and with more young workers (25-29 years) than aged workers. These findings provide an indication to the parties involved such as employees, employers and the government, that the health of employees significantly affects health expenses, and can have a huge impact on the nation’s economy.